Decision Support for New Employee Admissions With Profile Matching And Electre Methods - Sri Rahajeng, Dini Estu; Al Amin, Iman Husni (Universitas Negeri Semarang, 2021)
Purpose: Employee turnover at large companies is something that often occurs which can result in losses to the company. Difficulties experienced by the company in selecting prospective new employees have resulted in employees being hired not following company expectations. Because of this, we need a decision support system that can help to recommend prospective new employees who match the company's criteria.Â Methods: The profile matching method is used to determine the alternative values and criteria from the aspects of personality, job aspects, attitudes, and social aspects of prospective new employees, while the Electre method is used to improve the ranking of the best prospective employees.Â Result: By eliminating the alternative value = 1 on the line, each line is a candidate who is declared accepted with the best alternative value.Â Novelty: Research on decision support systems for new employee recommendations has been done a lot, but no one has combined methods Profile Matching and Electre in one system.